Biblical Deborah and Mary Mitchell Slessor â€“ A Comparison in Time and Space - Eyo, Ubong E. (Universitas Negeri Makassar, 2020)
This paper investigates â€œBiblical Deborah and Mary Mitchell Slessor â€“ A Comparison in Time and Space and Lessons for Contemporary Africa.â€ Worthy of note is the fact that, for some of the religions of the world women are a problem; from time immemorial they have been subordinate to men, second-class in the family, politics and business, with limited rights and even limited participation in worship. This was not different from the epochs of both biblical Deborah (Judges 4-5) and Mary Mitchell Slessor, the White Queen of Okoyong. In the time where patriarchy was the rule of the day, there arose two women at different places, times yet with similar circumstances to salvage the people and bring about Godâ€™s mission to the human race. Though both operated within the context of the mission of the church, theirs was missio dei not missio ecclesia, because in their age, missio ecclesia used more of patriarchal instruments while mission dei was/is involve in using human and the entire inhabited world (oikoumenÄ“). The peculiar things about the epochs of both Deborah and Mary Slessor are best described in the text,